Molekul Major Histocompatibility Complex (MHC) Klas II pada Epitel Usus: Presentasi Antigen Luminal? - Y. Andwi Ari S, Y. Andwi Ari S (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
The major histocompatibility complex (MHC) class II antigens were originally described to be expressed on the surface of B lymphocytes, macrophages, skin Langerhans cells (LC) and dendritic cells (DC). Surprisingly, the class Il molecules of MHC are also found in the intestinal epithelium.The distribution and expression of la molecules on intestinal epithelial cells depend on the continuous exposure of antigen and the presence of certain stimuli, like interferon-gamma, inflammation process in the gut and graft-versus-host disease. The function of class II molecules on intestinal epitheliurn may be different from those molecules on professional antigen presenting cells. Luminal antigens which are processed by enterocytes will be delivered to CD8 cells in the vinous epithelium and led to immunosuppression, whereas antigen uptake by M cells in the Peyers patches will be presented to CD4 cell populations, and initiate the immune response.Key Words : antigen processing-MHC molecule-enterocytes-Peyers patches-mucosal immunity